Municipal solid waste governance: development and application of an index embodying the Global South context - Sasahara, Camila; Rodrigues, Letícia Stevanato; Cetrulo, Tiago Balieiro; Gimenez, Bianca Gabani; Alencar, Melanie Vianna; Elliff, Carla Isobel; Cetrulo, Natália Molina; Gonçalves Dias, Sylmara Lopes Francelino; Conti, Luis Americo; Scrich, Vitória Milanez; Turra, Alexander (Frontiers in Sustainability, 2024)
The quality of municipal solid waste governance is a key public issue associated with environmental, social and health concerns. This paper aimed to develop a Municipal Waste Governance Index to support the assessment and monitoring of municipal solid waste management in municipalities of the Global South. The development of the Municipal Waste Governance Index comprised six stages: definition of a theoretical framework for monitoring MSW governance, data selection and usability analysis, normalization, weighting, and aggregation through statistical and participatory methods and, finally, classification and visualization of results in dimensions and an index. The dimensions of the Municipal Waste Governance Index are: Regulatory Quality, Voice and Accountability, and Government Effectiveness. After defining the steps and dimensions of the Municipal Waste Governance Index, a case study was performed with Brazilian municipalities. The results of the study show that most municipalities have medium Government Effectiveness, low Voice and Accountability, and high and very high Regulatory Quality. Furthermore, these results identify critical points in municipal solid waste governance in the Global South, such as Voice and Accountability concerning formal structures of social participation and the informal system, which includes waste pickers, and existing data, completeness and consistency of the database for accountability; and in Government Effectiveness which is primarily associated with socioeconomic development. Despite the high Regulatory Quality condition in Brazil, municipal solid waste governance does not reflect it, but rather the mechanisms of participation, accountability, and quality of public services performed in municipalities.This academic research has practical potential consequences, concerning the improvement of MSW governance in municipalities of the Global South.